Design of Water Distribution System: Appropriateness of Structured System in Large Irrigation Projects in Nepal - Adhakari, Basistha (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Many large irrigation projects in Nepal operate under command area development works that emphasize on-farm water distribution and management. These projects have specific design characteristics that were planned to comply with available water resources, climatic conditions, soil type, and water distribution technology. The water distribution technologies differ based on the design needs of each individual project and the design preferences of various foreign consulting firms. This article focuses on the issues of planning and designing water distribution systems of large irrigation systems at the irrigation service delivery level. The layout planning of an irrigation system is an important aspect of design for water distribution, typically guided by hierarchical system. This article also highlights the existing canal hierarchy of these systems and their appropriateness for efficient water distribution. Furthermore, the appropriateness of the structured system is also examined in the Sunsari Morang Irrigation Project. The article concluded with some suggestions for planning and designing command area development works of forthcoming large irrigation projects such as the Sikta Irrigation Project, the Babai Irrigation Project, and the Mahakali Irrigation Project Stage-III. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 25-30